2012
DOI: 10.1002/smll.201200738
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Polymer Templating Route Toward High‐Aspect‐Ratio Crystalline Titania Nanostructures

Abstract: High-aspect-ratio rutile and anatase hybrid nanowires are produced via a template-directed process using a novel cylindrical polyelectrolyte brush template. Loading the highly negatively charged 1D templates with pre-synthesized TiO(2) nanocrystals, results in the fabrication of soluble crystalline TiO(2) hybrid nanowires.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 56 publications
0
43
0
Order By: Relevance
“…Titanium oxide surfaces were modified by polymeric species either to tune their charging and aggregation behaviour or to functionalize them to prepare hybrid materials [30,[80][81][82] or to enhance the adsorption capacity of the particles [26,83,84]. It was shown that polymer coating improves the cellular uptake of the particles in biomedical applications [6].…”
Section: General Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…Titanium oxide surfaces were modified by polymeric species either to tune their charging and aggregation behaviour or to functionalize them to prepare hybrid materials [30,[80][81][82] or to enhance the adsorption capacity of the particles [26,83,84]. It was shown that polymer coating improves the cellular uptake of the particles in biomedical applications [6].…”
Section: General Remarksmentioning
confidence: 99%
“…Colloidal stability of the particles is a key issue in photocatalytic applications, where stable dispersions of primary particles are required during the catalytic process, while aggregation, that is, destabilization of the dispersions, can be induced to eliminate the solid material by subsequent sedimentation and filtration [16,28,29]. To tune the stability of the heterogeneous systems, numerous stabilizing or destabilizing agents including simple salts or polymeric compounds have been already applied and comprehensive studies were published to describe the influence of the additives on the colloidal stability of the titanium oxide materials [5,[30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to TiO2 crystallites, TiO2 with 1D or 2D nanostructure, such as rods, belts and tubes, is considered to have some advantages in electronic and photonic devices [45][46][47]. Rutile nanorods with the length controlled by the hydrothermal reaction time were fabricated in Park's group [48].…”
Section: Methodsmentioning
confidence: 99%
“…To increase specific surface area, nanocrystalline metal oxide precursors may be aligned at the mesoscale. [7][8][9][10][11] This can be achieved by a template assisted route in the presence of surfactants or block copolymers. [12][13][14] To fully exploit the potential of these materials for most applications the template has to be removed.…”
mentioning
confidence: 99%